Recombinant Lactococcus lactis Carrying IL-4 and IL-10 Coding Vectors Protects against Type 1 Diabetes in NOD Mice and Attenuates Insulitis in the STZ-Induced Model - Tatiane M. Preisser; Vanessa P. da Cunha; Mariana P. Santana; Vanessa B. Pereira; Denise C. Cara; Bianca M. Souza; Anderson Miyoshi (Journal of Diabetes Research)
Type 1 diabetes (T1D) is an autoimmune disease that culminates in beta cell destruction in the pancreas and, subsequently, deficiency in insulin production. Cytokines play a crucial role in the development of diabetes, orchestrating the recruitment and action of immune cells, to not only destroy insulin-producing cells but also preserve them. Therefore, the aim of this study was to investigate the effect of orally administered Lactococcus lactis MG1363 FnBPA+ strains carrying plasmids encoding IL-4 and IL-10 in the streptozotocin- (STZ-) induced diabetes model and in nonobese diabetic (NOD) mice. The STZ-induced mice that were treated with combined bacterial strains carrying plasmids encoding IL-4 and IL-10 showed lower incidence of diabetes and more preserved pancreatic islets than the mice that received the individual bacterial strains. Combined administration of L. lactis MG1363 FnBPA+ (pValac::dts::IL-4) and L. lactis MG1363 FnBPA+ (pValac::IL-10) resulted in protection against diabetes in NOD mice. It was shown that the combined treatment with recombinant bacterial by oral route prevented hyperglycemia and reduced the pancreatic islets-destruction in NOD mice. In addition, increased levels of IL-4 and IL-10 in serum and pancreatic tissue revealed a systemic effect of the treatment and also favored an anti-inflammatory microenvironment. Reduced concentrations of IL-12 in pancreas were essential to the regulation of inflammation, resulting in no incidence of diabetes in treated NOD mice. Normal levels of intestinal sIgA after long-term treatment with the L. lactis strains carrying plasmids encoding IL-4 and IL-10 indicate the development of oral tolerance and corroborate the use of this potent tool of mucosal delivery. For the first time, L. lactis MG1363 FnBPA+ strains carrying eukaryotic expression vectors encoding IL-4 and IL-10 are tested in STZ-induced and NOD mouse models. Therefore, our study demonstrates this innovative strategy provides immunomodulatory potential for further investigations in T1D and other autoimmune diseases.